2008
DOI: 10.1667/rr1067.1
|View full text |Cite
|
Sign up to set email alerts
|

MDR1Gene Transfer Using a Lentiviral SIN Vector Confers Radioprotection to Human CD34+Hematopoietic Progenitor Cells

Abstract: Tumor radiotherapy with large-field irradiation results in an increase in apoptosis of the radiosensitive hematopoietic stem cells (CD34(+)). The aim of this study was to demonstrate the radioprotective potential of MDR1 overexpression in human CD34(+) cells using a lentiviral self-inactivating vector. Transduced human undifferentiated CD34(+) cells were irradiated with 0-8 Gy and held in liquid culture under myeloid-specific maturation conditions. After 12 days, MDR1 expression was determined by the rhodamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Therefore, blocked MDR1 may enhance the efficacy of chemotherapy and reverse radioresistance in patients. Maier et al (29) confirmed that a protective effect of retroviral overexpression of MDR1 is increasing the radiotolerance of haematopoietic cells and the related apoptosis gene was downregulated. In the present study, it was also observed that MDR1 was a radioresistant factor which could be downregulated by mir-593.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, blocked MDR1 may enhance the efficacy of chemotherapy and reverse radioresistance in patients. Maier et al (29) confirmed that a protective effect of retroviral overexpression of MDR1 is increasing the radiotolerance of haematopoietic cells and the related apoptosis gene was downregulated. In the present study, it was also observed that MDR1 was a radioresistant factor which could be downregulated by mir-593.…”
Section: Discussionmentioning
confidence: 94%
“…Lentivirus-mediated MDR1 overexpression in human CD34 + cells may increase the radiation tolerance of the hematopoietic system (Maier et al, 2008). Transduction of the MDR1 gene into hematopoietic stem cells suggests a bone marrow-protective effect with no serious side-effects observed (Takahashi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…VIII) was described previously. 31,38 For cloning of the other five bicistronic vectors see Supplementary Methods.…”
Section: Cloning Of Vectorsmentioning
confidence: 99%
“…38 HL-60 and K562 cells were transduced (with an multiplicity of infection of 3) and selected by vincristine (20 nM) or BCNU (40mm) according to standard operating procedures. 31 HSCs were pre-stimulated as described previously; 31 then cells were transduced three times (each with an multiplicity of infection of 10) during 24 h as described previously 31 for experiments shown in Figure 3 or according to the protocol of Santoni de Sio et al 39 for experiments shown in Figure 4 with Iscove's modified Dulbecco's medium supplemented with 300 ng ml À 1 human stem cell factor, 300 ng ml À 1 fms-like tyrosine kinase receptor-3 ligand, 100 ng ml À 1 thrombopoietin, 60 ng ml À 1 interleukin-3 (all from R&D systems, Wiesbaden, Germany), 8 mg ml À 1 polybrene (Sigma-Aldrich) and 0,75 mM MG-132 (Merck4Biosciences, Darmstadt, Germany).…”
Section: Viral Work and Detection Of Transduced Cellsmentioning
confidence: 99%